The day my mother left - Prosek, James 1975- (Simon & Schuster Books for Young Readers, 2007)
When his mother leaves to live with another man, nine-year-old Jeremy faces his own pain and loss, his father's depression and sister's distance, the pity of friends and strangers, and his father's remarriage two years later, finding solace in fishing and his artwork.